(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Primary open-angle glaucoma (POAG) is a leading cause of irreversible blindness, characterized by progressive optic neuropathy and retinal nerve fiber layer (RNFL) thinning. Trabeculectomy, a common surgical intervention to lower intraocular pressure (IOP), aims to slow disease progression. Evaluating RNFL thickness before and after trabeculectomy using OCT is crucial to understanding the surgery’s impact on optic nerve health. Aim This study aims to assess the RNFL thickness in primary open-angle glaucoma (POAG) before and one month after trabeculectomy surgery using optical coherence tomography (SD-OCT). Method A group of patients aged 40-60 years who attended the Department of Ophthalmology at Bangladesh Medical University and were diagnosed with POAG comprised this prospective observational pre–post study’s patients. 20 eyes of 20 patients were selected for the study group. The study duration was one year. A complete clinical evaluation was conducted, including intraocular pressure (IOP) measurement before and one month after surgery. Optical coherence tomography (OCT) RNFL was performed preoperatively and postoperatively in the ophthalmology department. Statistical analysis of the results was conducted using computer-based software, SPSS 22. A probability ‘P’ value of 0.05 or less was considered significant. Results It was observed that most of the patients (90%) belonged to the age group of 51–60 years, mean age was 57.1±4.12 years. More than half of the study patients were male (55.0%), while 45.0% were female. In terms of glaucoma severity, 60.0% had severe glaucoma, remaining had mild and moderate glaucoma. The mean preoperative intraocular pressure (IOP) was 18.9±3.73 mmHg, while the mean postoperative IOP was 14.2±2.1 mmHg. A significant (p<0.05) reduction in IOP was observed postoperatively compared to the preoperative period. Regarding retinal nerve fiber layer (RNFL) thickness, the superior RNFL thickness was 75.2±23.7 preoperatively and 81.6±25.29 postoperatively. The mean overall RNFL thickness was 60.65±10.34 preoperatively and 63.85±12.74 postoperatively. A significant (˂0.05) increase was observed in superior and mean RNFL thickness postoperatively compared to the preoperative period. But in other quadrants, there were changes in RNFL thickness, but the changes weren’t statistically significant (˃0.05). Conclusion This study assessed RNFL thickness changes before and after trabeculectomy in primary open-angle glaucoma. A significant reduction in IOP was observed postoperatively. Superior and mean RNFL thickness increased notably, while inferior, nasal, and temporal regions showed mild changes. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 871-879